THE EFFECT OF USING BIG BOOK MEDIA ON LEARNING INTEREST AND LEARNING RESULTS OF SOCIAL SCIENCE - Lisa Bela; Nursalam; Idawati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to determine the use of Big Book media toward students' interest and learning outcomes in social science. This research used a quantitative approach and quasi-experimental research type. The data collection techniques used were: questionnaires, tests, and documentation. The Kolmogorov-Smirnov test and the Homogeneity of Variances test were operated to answer the formulation of the problem, and finally T-test was operated to test the hypothesis that has been proposed. The results of this study were: (1) there was a significant influence between Big Book media on social studies interests as evidenced by the tcount> t table (7,656> 2,0003) and the t significance value for the questionnaire variable was 0,000; this value was smaller than the probability 0.05 (0.000 <0.05); (2) there was a significant influence between Big Book media on social studies learning outcomes as evidenced by the value of tcount> t-table (3.982> 2.0003) for the T-test variable. The significance value of t for the test variable was equal to 0.000 and this value was smaller than the probability of 0.05 (0.000 <0.05); and (3) there was a significant influence between Big Book media on the social studies learning interest and learning outcomes as evidenced by the value of tcount> ttable (7,656> 2,0003) for the questionnaire variable, while for the test variable (3,982> 2,0003). The significance value of t for the questionnaire and test variables was both 0,000 and this value was is smaller than the probability of 0.05 (0,000 <0.05)